Webmetric study of Ibero-america National Archives: Heuristic evaluation vs Automatic evaluation - Sanz Caballero, Isabel María; Faba Pérez, Cristina (Revista General de Información y Documentación, 2018)
The purpose of this paper is twofold: to obtain the Quality rankings of the National Archives websites in Ibero-America (Spain, Portugal and Latin America), following the implementation of weighted models of general and specific subjective characteristics (Heuristic models ) and automatic (Automatic models) models designed in the present investigation, and on the other, to verify if there is a correlation between these Rankings and different indicators of the country where the Archive is located, as well as between the Rankings found through the Heuristic evaluation and the Automatic evaluation. To do this, we designed the weighted model of characteristics that allows the specific evaluation of the archival web sites, in addition to an exhaustive template of characteristics to perform both evaluations. The results show greater compliance in the case of the general and automatic characteristics, a substantial and moderate direct relationship between the Heuristic ranking and the country’s indicators, and the reverse between the Automatic ranking and these indicators; And a moderate inverse correlation between the Heuristic and Automatic ranking, which allows to conclude that it is necessary to design websites that are more archives oriented and to combine both types of valuations to obtain more accurate results.